Tehničke inovacije Ervin G. Erdösa: mechanički transduktor za izotonične mišićne kotrakcije - Igić, Rajko (Scripta Medica, 2022)
I wrote on the renowned pharmacologist Professor Ervin G Erdös and his scientific opus in my reminiscence article written on the occasion of his death in 2019.1 When I attended the Fourth International Congress in Pharmacology in Basel in 1969, Dr Ervin G Erdös invited me to join his laboratory. Thus, in April 1970, I arrived in Oklahoma City as a Fulbright Fellow to work with him for two years. Later on, as a visiting scientist I frequently worked in his research laboratories in Dallas and Chicago and we shared research interests through visits across the Atlantic between the former Yugoslavia and the United States.2, 3